2018
DOI: 10.18203/2319-2003.ijbcp20183486
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Pattern and drug utilization study in inpatients of department of Orthopaedics in a rural teaching hospital of Ujjain, Madhya Pradesh, India

Abstract: Background: Drug utilization study can increase our understanding of how drugs are being used. This study was done to evaluate the current drug prescribing trend in management of indoor patient of orthopaedic department and to comment on rationality of the prescribed medicines.Methods: This is a prospective observational study conducted for 12 months, in Chandrikaben Rashmikant Gardi Hospital, a 600 bedded tertiary care rural based, teaching hospital. Total 611 patients were included in this study.Results: Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
1
0
1
Order By: Relevance
“…(23%) were diagnosed with pain in knee, (20%) patients with Pain in upper limb, (10%) with fracture while (5%) cases were diagnosed as osteoarthritis which was least no of diagnosed cases. These findings were different to the findings of Baghel R et al 8 who reported fracture as the most common diagnosis however osteoarthritis was the least diagnosed cases in both the study. None of the study was found in the literature who reported pain as the most common diagnosis.…”
Section: Diagnosiscontrasting
confidence: 99%
See 2 more Smart Citations
“…(23%) were diagnosed with pain in knee, (20%) patients with Pain in upper limb, (10%) with fracture while (5%) cases were diagnosed as osteoarthritis which was least no of diagnosed cases. These findings were different to the findings of Baghel R et al 8 who reported fracture as the most common diagnosis however osteoarthritis was the least diagnosed cases in both the study. None of the study was found in the literature who reported pain as the most common diagnosis.…”
Section: Diagnosiscontrasting
confidence: 99%
“…In our present study among 100 patients (n=100) studied who were undergoing treatment with different kinds of drugs in orthopedic department, it was observed that Male (58%) were predominant than females (42%). The present study findings were almost similar to the study done by Srividya BP et al 7 and Baghel R et al 8 who reported prevalence of more than female. However, our study results were contradictory to the findings of Shivaleela B et al 7 who reported more cases of female patients in their study where they did their study in postoperative patients in different surgical departments including orthopedic department.…”
Section: Gender and Age Distributionsupporting
confidence: 92%
See 1 more Smart Citation
“…The WHO core prescribing indicators measure the performance of health-care providers in various dimensions related to the appropriate use of drugs. Based on the WHO prescribing indicators, most of the prescriptions encountered in this study were deficient in the standard requirement set by the WHO, similar findings were reported by studies done earlier [2,10,13]. The WHO suggested prescribing indicators consider an average number of drugs per prescription as an important parameter indicating polypharmacy.…”
Section: Abhilash Et Alsupporting
confidence: 86%
“…When we compared the average number of drugs (4.84) prescribed in our study was found to be more than several other studies i.e. 3.5 in Alshakka et al [16], 1.33 in Das et al [17] and 1.9 in Shankar et al [18] study, at par (4.72) with Mishra R et al [19] and less than (8.86) that of Baghel R et al [20] study.…”
Section: Discussioncontrasting
confidence: 44%